Cathodal Occipital tDCS Is Unable to Modulate the Sound Induced Flash Illusion in Migraine - Maccora, Simona; Giglia, Giuseppe; Bolognini, Nadia; Cosentino, Giuseppe; Gangitano, Massimo; Salemi, Giuseppe; Brighina, Filippo (Frontiers in Human Neuroscience, 2019)
Migraine is a highly disabling disease characterized by recurrent pain.Despite an intensive effort, mechanisms of migraine pathophysiology, still represent an unsolved issue. Evidences from both animals and humans studies suggest that migraine is characterized by hyperresponsivity or hyperexcitability of sensory cortices, especially the visual cortex. This phenomenon, in turn, may affect multisensory processing. Indeed, migraineurs present with an abnormal, reduced, perception of the Sound-induced Flash Illusion (SiFI), a crossmodal illusion that relies on optimal integration of visual and auditory stimuli by the occipital visual cortex. Decreasing visual cortical excitability with transcranial direct current stimulation (tDCS) can increase the SiFI in healthy subjects. Moving from these issues , we applied cathodal tDCS over the visual cortex of migraineurs, with and without aura, in order to decrease cortical excitability and thus physiologically restoring the perception of a reliable SiFI. Differently from our expectations tDCS was unable to reliably modulate SiFI in migraine. The chronic, relatively excessive, visual cortex hyperexcitability, , featuring the migraineur brain, may render tDCS ineffective for restoring multisensory processing in this disease.